Driven by FOMO: how the fear of missing out shapes information-seeking behaviors in university students - Muhammad Rifky Nurpratama (Program Studi Ilmu Perpustakaan dan Informasi Islam, Fakultas Tarbiyah dan Keguruan, Universitas Islam Negeri Antasari Banjarmasin, 2026)
This study examines the relationship between the Fear of Missing Out (FOMO) and information-seeking behavior among undergraduate students in the Faculty of Humanities, Universitas Diponegoro. Grounded in Self-Determination Theory and the Information Search Process model, the study explores how unmet psychological needs influence students’ motivations to seek information. A quantitative research design was employed using a structured questionnaire for 364 students selected through simple random sampling. Data were analyzed using simple linear regression with SPSS software. The analysis revealed a strong positive correlation between FOMO and information-seeking behavior, explaining 68.4% of the variance. Students with higher FOMO levels demonstrated more frequent and intensive information-seeking activities, indicating that FOMO serves as an emotional and psychological driver. The study concludes that FOMO significantly influences students’ information-seeking behavior. These findings provide practical implications for university administrators in helping students develop healthier information-seeking strategies. Further longitudinal research is recommended to establish causal relationships and explore how digital platform interactions shape these behaviors over time